Parametric optimization of biogas potential in anaerobic co-digestion of biomass wastes. (15th March 2021) - Vijin Prabhu, A.; Antony Raja, S.; Avinash, A.; Pugazhendhi, Arivalagan
Graphical abstract: Highlights: Anaerobic co-digestion of biomass wastes and cow manure was conducted. Response surface methodology was used to optimize the operating parameters of pH and temperature. The anaerobic co-digestion process was mainly dependent on pH change than temperature change. The experimental response value was well in agreement with the optimal predicted response value. The actual methane yield of 396.0 ± 6 L/kgVS, 76.6% of anaerobic biodegradability, and total solid reduction of 41.1%. Abstract: The effect of anaerobic co-digestion of Prosopis juliflora seeds, water hyacinth, dry leaves, and cow manure on the biogas production performance was assessed in the present study. The research was optimized by central-composite design and methodology of the response surface to optimize the operating parameters of pH and temperature. Average biogas production, cumulative biogas yield, and methane content had a significant impact on pH and T variation results. Good linear regressions were observed between the predicted and experimented responses. We found a unique operating condition (pH = 7.034, and T = 35.557 °C) to achieve the maximum value of each responses. In all tests, the anaerobic biodegradability was observed within the range of 14.7–72.6%. The experiment conducted on the predicted operating condition resulted in actual methane yield (AMY) of 396.0 ± 6 L/kgVS, anaerobic biodegradability of 76.6%, and the TS reduction of 41.1%.